THE ROLE OF SPACED REPETITION AND RETRIEVAL PRACTICE IN SUPPORTING LONG-TERM L2 VOCABULARY DEVELOPMENT (SCIENCE TIME JOURNAL, 2026)
This article explores how spaced repetition and retrieval practice contribute to long-term vocabulary growth in second language (L2) learning. Drawing on recent experimental studies and meta-analytic findings, the paper compares distributed learning strategies with traditional massed learning methods. The findings demonstrate that learners retain vocabulary more effectively when they revisit and actively recall words over spaced intervals rather than studying them intensively in a single session. In addition to improving retention, spaced retrieval practice supports more sustainable lexical development over time. The article also discusses how these strategies can be integrated into classroom teaching and digital learning environments.